Comments on the plant and animal names mentioned in Hesiod’s "Works and days" - de Toledo, Reynaldo Cícero (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
In his poem "Works and days", the Greek poet Hesiod, who flourished in the 8th Century BC, highlights the role of honest work in people’s lives, defends justice, and advises farmers regarding farming techniques. The poet mentions plants and animals of great everyday importance for rural workers, at times associating them to work, justice or changes of the seasons. The purpose of this article is to collect the phytonyms and zoonyms mentioned in Hesiod’s poem, and in the writings of later Greek and Latin authors that also cited them, focusing on an onomatological analysis. For that reason, historical and taxonomical information related to the selected terms are included, in addition to etymological and semantic information, gathered from linguistic and specialized dictionaries in the biological and medical areas, as well as from pertinent books and scientific articles. Besides that, various correlating terms used in the scientific literature were succinctly analyzed in order to demonstrate that these classical names and their derived forms continue to be used in scientific onomatology today.